Examining the White Karelian textile tradition of the late nineteenth century – focus on plant fibers - Suomela, Jenni A.; Vajanto, Krista; Räisänen, Riikka (TEXTILE, 2020)
Collection SU4522 in the Finno-Ugric Collections of the National Museum of Finland consists of 143 items, mainly textiles from nineteenth-century White Karelia, now part of the current Russia. Forty-one linen textiles were chosen for closer examination, with the aim of evaluating the area's textile culture and identifying the materials using microscopic methods. Flax, hemp and nettle have all been traditional materials for clothing in northern Europe. Additionally, cotton became established in the region during the nineteenth century. Previous research lacked such a deep examination of the textile materials used, leaving room for speculation. Stinging nettle has not been shown before to have been used as a textile material in the Karelian area. Our results show that it appeared commonly in ratsina-shirts and kaspaikka-towels. Against the consensus hemp was rare and appeared only in one of the items. The results are mirrored by concurrent pictorial and written material from I. K. Inha who visited the region in 1894 and collected most of the items in the collection. White Karelian textile traditions from clothing to fabrics, weaving, spinning and fiber production are discussed in the article. Nevertheless, questions concerning the origins of the materials and the effects of the peddling tradition would need further research. Peer reviewed